Mushroom residue modification enhances phytoremediation potential of Paulownia fortunei to lead-zinc slag. (August 2020) - Han, Liangze; Chen, Yonghua; Chen, Mingli; Wu, Yangfeng; Su, Rongkui; Du, Lu; Liu, Zhiming
Abstract: Phytoremediation is an effective strategy for the remediation of lead-zinc slag, while the response of plant on lead and zinc was less concerned. In this study, mushroom residue was adding in lead-zinc slag to enhance the phytoremediation potential of P. fortunei, the effects of three treatments (lead-zinc slag, red soil, lead-zinc slag + 10% (m/m) mushroom residue) on the growth, physiology and microstructure of P. fortunei were determined. The results showed that the addition of mushroom residue increased the biomass, plant height and chlorophyll concentration of P. fortunei, indicating that the addition of mushroom residue can facilitate the growth of P. fortunei . Moreover, the proportions of oxalate-Pb forms and phosphate-Zn were dominant in leaves and stems of P. fortunei . With the addition of mushroom residue, Pb and Zn were transformed to the extraction state with weak migration activity, which can reduce the damage level of Pb and Zn to P. fortunei . The results from scanning transmission electron microscopy (STEM) showed that, the mushroom residue amendment could maintain the integrity of the cell structural of P. fortunei. The results from fourier transform infrared spectrometer (FTIR) analysis showed that the mushroom residue amendment could increase the contents of proteins and polysaccharides in P. fortunei, which can combine with the metals. Clearly, the mushroom residue amendment could promote the growth ability of P. fortunei in lead and zinc slag and strengthen the phytoremediation potential. Graphical abstract: Image 1 Highlights: Mushroom residue can alleviate the toxicity of lead zinc slag to Paulownia fortunei . Mushroom residue can enhance the phytoremediation potential of Paulow nia fortunei in lead zinc slag. Mushroom residue can transform lead and zinc in Paulownia fortunei into weak migration state. Mushroom residue can increase the content of photosynthetic pigments in Paulownia fortunei leaves.